Targeted drug delivery to the inferior meatus cavity of the nasal airway using a nasal spray device with angled tip. (June 2022) - Zare, Farhad; Aalaei, Ehsan; Zare, Farzad; Faramarzi, Mohammad; Kamali, Reza
Highlights: The innovation of this work is using a nasal spray with angled tip for targeted drug delivery to the inferior meatus. Spray with angled tip has significant effects on particle injection pattern and streamlines. Indeed, it increases particle deposition in the inferior meatus. The majority of deposited particles in the inferior meatus have diameters in the range of 15–55 μ m and could be considered with spray designers. The results of this study could be used for the treatment of epiphora. Abstract: Background and Objective: Nowadays, by advancement in computational tools, Computational Fluid and Particle Dynamics (CFPD) technique can be used more than ever. The main aim of this study is using a nasal spray device with angled tip to deliver drug particles to the inferior meatus cavity for treatment purposes. In the present study, the drug delivery to the lower regions of the nasal cavity will be improved that has been considered less in the literature. Methods: For this purpose, a spray with an angled tip was used, and the deposition of sprayed particles was compared with a spray with a straight tip. Based on the objectives presented above, a realistic model of the nasal route, including facial geometry, and paranasal sinuses obtained from a series of Computed tomography (CT) scan images, as well as the geometry of a nasal spray with two types of tip were developed. Results: It is observed that by using the spray with the straight tip, particles were mainly deposited in the middle and superior regions of the nasal cavity and no particles entered the inferior meatus airway. The results proved that the spray with the angled tip improved the regional deposition percentage in the inferior meatus cavity up to 2.4% of the total sprayed particles and 1 mg drug mass delivered to this region. The majority of these particles had a diameter between 15–55 µm and that could be considered by spray designers to produce more compatible sprays with the targeted region. Also, most particles were deposited near the inferior meatus cavity and so there is a strong chance to be absorbed and delivered to this region. Conclusion: The deposition pattern and particle size contour due to the spray with the angled tip can give sight to the designers and producers of nasal sprays to build more efficient types for better targeted drug delivery purposes. With this spray type, deposited particles were observed in the inferior meatus that never happened with the straight type. Also, the angled tip of the nasal spray shows the benefit of the ease of use for the user.